Eastern enlargement, migration and Euro adoption - Tito Boeri (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
Western Europe has welcomed its new members by shutting the door in the face of the workers coming from the East and making their road to EMU more difficult. Two years down the road of enlargement, some countries are now liberalizing worker flows. Indeed, as shown in this paper, these restrictions are not justified by migration pressures and rely on ill-founded concerns that nominal convergence could delay real convergence. Moreover, they are mutually inconsistent: delaying EMU convergence would just worsen labour market conditions with respect to a scenario of relatively rapid Euro convergence, by increasing real interest rates and negatively affecting FDI directed to the New Member States. This ultimately means that delaying EMU convergence may backfire in terms of stronger East-West migration pressures.
Keywords: 330; EU-Osterweiterung; Eurozone; Währungsunion; internationale Wanderung; Integrationspolitik; europäische Integration; Einwanderungspolitik; Konvergenz; Protektionismus; Wanderungspotenzial; Ost-West-Wanderung; Europäische Union; Osteuropa; Mitteleuropa